Increasing the Learning Independence of Students Experiencing Learning Difficulties Through the Peer-Mediated PJBL Model - Hermawan, Budi; Hufad, Achmad; Rochyadi, Endang; Sunardi, Sunardi; Fatimatuzzahra, Ana; Ratnawati, Andayani (Angstrom Centre of Education, 2023)
Learning Independence is the ability of students to regulate themselves in learning. Project-based learning mediated by peers is a learning innovation in an inclusive setting to accommodate the diverse learning needs of students by fostering student independence. The purpose of this study was to reveal the effect of project-based learning on the learning independence of students with learning disabilities. This research uses a qualitative approach with data collection techniques using questionnaires, interviews, and observations. This research involved 9 schools in West Java. The results showed that peer-mediated project-based learning affected increasing children's learning independence, especially for children with learning difficulties in mathematics. The results of this study can be used as a reference in the implementation of learning mathematics to foster learning independence.